2018
DOI: 10.1177/1055665617732783
|View full text |Cite
|
Sign up to set email alerts
|

An Intraoral Appliance to Retract the Protrusive Premaxilla in Bilateral Cleft Lip Patients Presenting Late for Primary Lip Repair

Abstract: The protruding and deviated premaxilla in bilateral complete cleft lip and palate (BCL/P) patients causes a perplexing problem in achieving a tension-free primary lip closure. An innovative noninvasive active intraoral Fixed Pre-Surgical Cleft Orthopedic (FPSCO) appliance is presented that has enabled to successfully reposition the premaxillary segment to a more favorable position prior to the surgical repair in 4 BCL/P patients, who reported late for treatment with a mean age of 18 ± 3 months. All the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
(17 reference statements)
1
6
0
1
Order By: Relevance
“…Premaxilla deviation (Dev) significantly decreased because of the extraoral lip strapping and alveolar molding plate. This finding correlates with that of Vura et al (2018), who studied an innovative noninvasive active intraoral fixed presurgical left orthopedic appliance and found that the deviated premaxilla was corrected toward the midline in 4 patients with BCLP. Likewise, Rot significantly improved between all time points, where the alignment of the premaxilla became perpendicular to TT 0 after the modified KKU-NAM treatment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Premaxilla deviation (Dev) significantly decreased because of the extraoral lip strapping and alveolar molding plate. This finding correlates with that of Vura et al (2018), who studied an innovative noninvasive active intraoral fixed presurgical left orthopedic appliance and found that the deviated premaxilla was corrected toward the midline in 4 patients with BCLP. Likewise, Rot significantly improved between all time points, where the alignment of the premaxilla became perpendicular to TT 0 after the modified KKU-NAM treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Due to the rare incidence of BCLP relative to other forms of cleft lip/cleft palate (Hagberg et al, 1998), few studies have been conducted on presurgical orthopedic treatment for BCLP and various appliance designs used in both passive and active treatment methods (Bennun & Langsam, 2009;Li et al, 2014;Kiya et al, 2015;Vura et al, 2018). In 1993, Grayson's PNAM technique was developed, consisting of a nasal stent extending from the anterior flange of an intraoral molding appliance (Grayson et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The final sample comprised 77 children, divided into two groups: a cleft group and a noncleft group. of 13 The children with bilateral cleft were recruited from a total of 65 patients with clefts who were referred to the Cleft Treatment Centre in Szczecin in 2017 and underwent lip and palate surgical repair according to a similar operating protocol, which was as follows: a twostage lip repair at the age of three to six months, followed by hard and soft palate closure in one operation at the age of approximately 12 months. Two-stage lip repair procedure started from the side of the wider cleft fissure.…”
Section: Methodsmentioning
confidence: 99%
“…Bilateral complete cleft lip and palate (BCCLP) is considered the most serious clinical form of cleft lip and palate (CLP) [13]. The primary manifestations of bilateral cleft lip are a procumbent or rotated premaxilla with a significantly increased width of the alar base and widely spaced lip segments, and very short columella [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…To align the premaxillary segment with lateral alveolar segments, several dentofacial orthopedic devices were used [24]. In some cases, however, there were no responses from the orthopedic forces, especially in patients with age greater than 10 months [5].…”
Section: Introductionmentioning
confidence: 99%